Clinical significance of accurate identification of lymph node status in distant metastatic gastric cancer - Zhou, Rui (Oncotarget, 2015)
PURPOSE: The clinical consequences of accurately identifying lymph node (LN) status in distant metastatic gastric cancer (DMGC) are unclear. We aimed to determine the prognostic significance of N stage, positive LN (PLN) count, and the positive LN ratio (LNR). We also retrospectively compared survival outcomes of DMGC patients stratified by LN dissection (LND). RESULTS: LND was performed in 1593 patients. The CSS was significantly different between groups divided according to N stage, PLN, and LNR in DMGC patients who underwent LND. Lower LNR was an independent predictor of longer survival in all kinds of patients cohorts, whereas PLN was not such a predictor. PLN count correlated with LND number and LNR. No correlation existed between LNR and LND number. Undergoing LND and having a higher number of dissected LNs were associated with superior CSS. MATERIALS AND METHODS: Data from 1889 DMGC patients treated between 2004 and 2009, and documented in the Surveillance, Epidemiology, and End Results (SEER) registry, were reviewed. Pearson's correlation coefficient and the Chi-square test were used to study the relationships between LND number, PLN count, N stage, and the LNR. Cancer-specific survival (CSS) was evaluated using Kaplan-Meier analysis, with the log-rank test performed for univariate analysis (UVA) and the Cox proportional hazards model employed for multivariate analysis (MVA). CONCLUSION: LN metastatic variables play important roles in the prognostic evaluation and treatment decisions of DMGC patients. Accurate identification of LN status in DMGC patients is critical. LND performance is associated with increased survival and has clinical practicability.